Is sunspot activity a factor in influenza pandemics?. (2nd May 2016) - Qu, Jiangwen
Summary: Introduction : The 2009 AH1N1 pandemic became a global health concern, although fortunately, its worst anticipated effects were not realised. While the origins of such outbreaks remain poorly understood, it is very important to identify the precipitating factors in their emergence so that future pandemics can be detected as quickly as possible. Methords : Descriptive epidemiology was used to analyse the association between influenza pandemics and possible pandemics and relative number of sunspots. Non‐conditional logistic regression was performed to analyse the statistical association between sunspot extremes and influenza pandemics to within plus or minus 1 year. Results : Almost all recorded influenza/possible pandemics have occurred in time frames corresponding to sunspot extremes, or +/– 1 year within such extremes. These periods were identified as important risk factors in both possible and confirmed influenza pandemics (odds ratio: 3.87; 95% confidence interval: 1.08 to 13.85). Conclusions : Extremes of sunspot activity to within plus or minus 1 year may precipitate influenza pandemics. Mechanisms of epidemic initiation and early spread are discussed including primary causation by externally derived viral variants (from space via cometary dust). Efforts to construct a comprehensive early warning system for potential influenza and other viral pandemics that include analysis of sunspot activity and stratospheric sampling for viral variants should be supported. Copyright © 2016 John Wiley & Sons, Ltd.